Fostering Entrepreneurship and MSME Development through Targeted Interventions: Lessons from India’s Experience with MUDRA, Stand-up India, and Startup India - Satsangi, Neetu Singh; Raghuwanshi, Sandeep; Hasan, Arif; Sushma, R.; Tare, Unmekha; Khan, Danish; Kumar, Prabhat; Singhal, Abhishek (International Journal of Economics and Financial Issues, 2025)
This study examines the role of selected Entrepreneurship Development Programs (EDPs) in promoting Micro, Small, and Medium Enterprises (MSMEs) in India. Using secondary data from government sources, the study analyzes the performance of three key schemes: MUDRA, Stand-up India, and Startup India. Descriptive statistics and regression analysis are employed to assess the impact of these schemes on MSME growth indicators such as amount sanctioned, accounts created, and jobs reported. The findings suggest that the selected EDPs have a significant positive impact on MSME growth, with MUDRA emerging as the most effective scheme. The study provides important implications for policy makers and other stakeholders involved in promoting entrepreneurship and MSME development in India. However, the results should be interpreted in light of certain limitations such as the reliance on secondary data and the focus on a limited set of EDPs.